Toxoplasma gondii, suicidal behaviour and suicide risk factors in US Veterans enrolled in mental health treatment - Postolache, Teodor T; Duncan, Erica; Yen, Poyu; Potocki, Eileen; Barnhart, Meghan; Federline, Amanda; Massa, Nicholas; Dagdag, Aline; Joseph, Joshua; Wadhawan, Abhishek; Capan, Colt D; Forton, Cameron; et al. (Folia parasitologica, 2025)
Markers of chronic infection Toxoplasma gondii (Nicolle et Manceaux, 1908) have been associated with suicidal self-directed violence (SSDV). We present the results of the first study relating T. gondii IgG serology with suicide attempts and suicidal ideation in United States Veterans, known to have higher suicide rates than members of the general population. We also related T. gondii serology to SSDV risk factors, including valid and reliable measures of trait impulsivity, aggression, self-reported depression, and sleep disturbance. We recruited 407 Veterans enrolled at three Veterans Affairs Medical Centers with mean (S.D.) age = 45.6 (11.6) years; 304 men (74.7%); 203 with a history of SSDV and 204 with no history of any self-directed violence (SDV). Seropositivity and serointensity, categorised as high (top quartile) or low (lower three quartiles), were analysed in relationship to SSDV, suicidal ideation and clinical risk factors using age and gender-adjusted linear and logistic methods, after transformations and nonparametric tests when appropriate. Associations between seropositivity and SSDV and its risk factors were not significant in all groups. High serointensity, while not associated with SSDV or repeat suicide attempts, was positively associated with suicidal ideation, depression, impulsivity, and daytime dysfunction due to sleepiness (p < 0.05), but only in Veterans with a history of SSDV. In Veterans without a history of SDV, no associations were significant. These associations remained significant after adjustment for certain socioeconomic factors (i.e., income, homelessness, military rank). Including education in the model downgraded the statistical significance of suicidal ideation and depression to statistical trends, but the significance of associations with impulsivity and daytime dysfunction due to sleepiness remained. Major limitations include the cross-sectional design, overall low seropositivity within the sample, and potentially spurious results due to multiple comparisons. Thus, the results of this report need to be replicated in larger samples, ideally longitudinally.
Keywords: dospělí; impulsivity; Female; Toxoplasmosis; Adult; pokus o sebevraždu; ženské pohlaví; sleep impairment; Suicidal Ideation; lidé; sebevražedné myšlenky; Toxoplasma; Suicide, Attempted; Veterans; depression; Risk Factors; suicidality; Spojené státy americké; protilátky protozoální; Male; Antibodies, Protozoan; rizikové faktory; United States; veteráni váleční; toxoplazmóza; lidé středního věku; mužské pohlaví; Middle Aged; Humans